Yin Zhi Huang, a traditional Chinese herbal formula, ameliorates diet-induced obesity and hepatic steatosis by activating the AMPK/SREBP-1 and the AMPK/ACC/CPT1A pathways - Yao, Qunyan; Li, Shuyu; Cheng, Xinlai; Zou, Yanting; Shen, Yue; Zhang, Shuncai (Annals of translational medicine, 2020)
Background: Yin Zhi Huang (YZH) is a formula composed of Artemisia scoparia, Gardeniae fructus, Scutellaria baicalensis Georgi, and Lonicerae Japonicae Flos. Most of the components are eaten as food in Asia. Here, we evaluated the role of YZH on a high-fat diet (HFD)-induced obesity and hepatic steatosis. Methods: Male C57BL/6J mice were fed with normal-chow diet, HFD, and HFD with low- or high-dose YZH for 16 weeks. Body weight gain, adipose mass, and plasma lipids levels were measured to evaluate the effect of YZH on obesity. Liver weight and staining methods on liver tissues were used to determine hepatic steatosis. The expression of involved genes and proteins were screened with qRT-PCR and immunoblotting, respectively. Results: The results showed that YZH significantly reduced body weight gain, adipose mass, and the size of adipocytes, while did not affect food intake in HFD-fed mice. H&E staining, bodipy staining, and oil red O staining displayed that YZH alleviates hepatic lipid accumulation. It also effectively restored elevated plasma levels of triglycerides (TG), total cholesterol (TC), alanine aminotransferase, and aspartate aminotransferase in HFD-fed mice. Mechanistically, these effects of YZH have associated with a decrease of AMPK/SREBP-1 pathway-mediated de novo lipogenesis and an increase of AMPK/ACC/CPT1A pathwaymediated mitochondrial fatty acid β oxidation. Conclusions: YZH supplementation ameliorated diet-induced obesity and hepatic steatosis by decreasing AMPK/SREBP-1 pathway-mediated de novo lipogenesis and increasing AMPK/ACC/CPT1A pathwaymediated mitochondrial fatty acid β oxidation.
Gesehen am 21.04.2020